POLA ASUH ORANGTUA MUDA DALAM MEMFASILITASI KECERDASAN MAJEMUK ANAK SULUNG PADA POS PAUD BINA DARUL ARIFIN - Maudina Rachmania, - (2022)
ABSTRACT In this thesis the author will discuss the problems found in the PAUD Bina Darul Arifin Post, young parents who have the eldest child in other terms the first child, have various multiple intelligences. The eldest child in the aspect of multiple intelligences is superior to the other twenty-five children. In addition to finding information at the Bina Darul Arifin PAUD Post, the author found information on social media, young parents who have the eldest child often share their children's posts in guiding learning. Learning that is obtained at school, young parents repeat in guiding the learning of their eldest child at home through appropriate parenting patterns. The theory used in this thesis is the theory of multiple intelligences which was coined by Howard Gardner. In this study, it is expected to be able to dig up information directly from young parents in the application of parenting in facilitating the multiple intelligences of the eldest child. The method used in this research is to use a qualitative research approach with a case study method. Where the results of this study are young parents as research subjects applying their parenting pattern using the application of democratic parenting to facilitate the multiple intelligences of the eldest child, because parents believe that democratic parenting is able to make children study together with parents at home with no coercion full of comfort and fun. So that children are able to have various aspects of multiple intelligences. The two eldest children have more than four multiple intelligences. Keywords: Learning, Young Parents, Multiple Intelligences